2015
DOI: 10.5056/jnm14162
|View full text |Cite
|
Sign up to set email alerts
|

Role of Corticotropin-releasing Factor Signaling in Stress-related Alterations of Colonic Motility and Hyperalgesia

Abstract: The corticotropin-releasing factor (CRF) signaling systems encompass CRF and the structurally related peptide urocortin (Ucn) 1, 2, and 3 along with 2 G-protein coupled receptors, CRF1 and CRF2. CRF binds with high and moderate affinity to CRF1 and CRF2 receptors, respectively while Ucn1 is a high-affinity agonist at both receptors, and Ucn2 and Ucn3 are selective CRF2 agonists. The CRF systems are expressed in both the brain and the colon at the gene and protein levels. Experimental studies established that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 206 publications
(230 reference statements)
0
67
0
Order By: Relevance
“…62,84 Plenty of work has been done to verify the concept that MCs contribute to stress induced gut dysfunction. For example, MCs mediate stress induced intestinal barrier disruption [85][86][87] and visceral hypersensitivity 82,88,89 due to the release of tryptase, TNF-α, 86 and histamine. 82 Peripheral administration of H 1 R antagonists fexofenadine and ebastine are capable of reversing post stress visceral hypersensitivity in rats.…”
Section: Central Stress: Psychological Distress and Negative Life Eventsmentioning
confidence: 99%
“…62,84 Plenty of work has been done to verify the concept that MCs contribute to stress induced gut dysfunction. For example, MCs mediate stress induced intestinal barrier disruption [85][86][87] and visceral hypersensitivity 82,88,89 due to the release of tryptase, TNF-α, 86 and histamine. 82 Peripheral administration of H 1 R antagonists fexofenadine and ebastine are capable of reversing post stress visceral hypersensitivity in rats.…”
Section: Central Stress: Psychological Distress and Negative Life Eventsmentioning
confidence: 99%
“…4 Stress induces changes of colonic functions, including increase of permeability, mucus secretion, motility, myenteric nerve activation, serotonin release, and the development of visceral hypersensitivity in rats. [5][6][7] In particular, water avoidance stress (WAS) is a well-known animal model of stress that increases the psychological component and imitates the experience of ongoing environmental life in humans. 8 It has been revealed that WAS increased fecal pellet output (FPO), colonic mast cell count, mucosal cytokine levels, and intestinal permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that an important factor in the pathogenesis of non-erosive reflux disease (NERD), functional dyspepsia, and IBS may be hyperresponsiveness to stress in the gastrointestinal tract. 9,[12][13][14] In daily life, we experience various symptoms due to excessive "stress" on the body. When the human brain perceives stress, CRH is released from the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Gastrointestinal physiologies, such as colonic motor and sensory functions, are known to be altered by stress induced by intravenous administration of CRH in patients with irritable bowel syndrome (IBS). 8,9 This evidence suggests that altered brain-gut interactions resulting from a magnified response to CRH lead to changes in colonic functions and could be relevant to the pathophysiology of IBS. However, the influence of CRH on the esophagus has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%